2015
DOI: 10.1097/mpa.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Biomedical Imaging, Bioengineering, and Related Technologies for the Development of Biomarkers of Pancreatic Disease

Abstract: A workshop sponsored by the National Institute of Diabetes and Digestive and Kidney Diseases and the National Institute of Biomedical Imaging and Bioengineering focused on research gaps and opportunities in the development of new biomarkers of pancreatic disease. The session was held on July 22, 2015, and structured into six sessions: 1) introduction and overview, 2) keynote address, 3) new approaches to the diagnosis of chronic pancreatitis, 4) biomarkers of pain and inflammation, 5) new approaches to the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…It should be noted that, in our series, the mean number of EUS criteria was 4.6 and more advanced stages were excluded as they did not meet the inclusion criteria. The optimal number of parenchymal and ductular abnormalities for a diagnosis of CP by EUS have been established with a high sensitivity and specificity (3,4), but when evaluating patients with early stage disease sensitivity it was reduced to 86% (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that, in our series, the mean number of EUS criteria was 4.6 and more advanced stages were excluded as they did not meet the inclusion criteria. The optimal number of parenchymal and ductular abnormalities for a diagnosis of CP by EUS have been established with a high sensitivity and specificity (3,4), but when evaluating patients with early stage disease sensitivity it was reduced to 86% (24).…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic elastography associated with EUS is currently considered to be a complementary and useful tool in diagnosing CP, and could even classify patients according to severity (23,24). However, whether less invasive capacity techniques, such as percutaneous ARFI based elastography, could be equally relevant needs to be systematically determined.…”
Section: Introductionmentioning
confidence: 99%
“…Recent modeling studies of future assay performance cite a minimum sensitivity of 88% and specificity of 85% to prolong patient survival and demonstrate cost effectiveness(2). Various approaches to achieve this are being explored(5; 6), including the use of CA242(3), circulating tumor cells(7), circulating tumor-derived extracellular vesicles including exosomes(8), metabolites(9), proteomic analyses(10; 11) and circulating DNA(12). Beyond the inherent technical challenges of these advanced analyses, a key question is whether early reported findings can be validated independently in larger sets of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Histologically, PDAC is a hard mass characterised by a marked desmoplastic reaction and build-up of fibrotic tissues [22]. MFP is also characterised by perilobular fibrosis, but with significantly lower mean collagen content compared with pancreatic carcinoma or tumour-associated chronic pancreatitis [23; 24], which suggests that the stiffness of MFP should be less than that of PDAC [17; 22; 25; 26]. Previous elastography studies based on EUS have indicated that the stiffness ratio between tumour and surrounding parenchyma is a useful metric for differentiating solid pancreatic masses [27; 28].…”
Section: Introductionmentioning
confidence: 99%